Burden of Proof - Bunn, T. Davis 1952- (Thorndike, Maine : Center Point Large Print, 2021)
"Ethan missed the chance to save his brothers life. When his brothers widow reveals that she and her husband were involved in a legal case that threatens the global power structure, Ethan must face his past and join the search for answers to discover how to redeem his future"--
Keywords: Time travel -- Fiction; Families -- Fiction; Brothers -- Death; Fiction; Fiction; Legal stories; Christian fiction